Optimalisasi website desa slamparejo melalui pelatihan jurnalistik untuk mewujudkan transparansi dan informasi publik - Fadhilah, Moh Nur (Maliki Interdisciplinary Journal, 2025)
A village website is one of the media information tools that can enhance transparency in village governance and provide easier access to information for the wider community, particularly in Slamparejo Village. However, the management of village websites often faces obstacles due to the lack of skills among village officials and the komunita informasi masyarakat (kim) in managing accurate and engaging information. Journalistic training is a strategic solution to improve the ability of village officials to compile and present information through the village website. This study aims to analyze the impact of journalistic training on optimizing the Slamparejo Village website and its effectiveness in increasing transparency and public information openness. The research method used is descriptive qualitative with a case study approach. The results show that journalistic training significantly contributes to improving the quality of website content and strengthening the role of the website as a means of transparency and communication with the community. Therefore, sustainable journalistic training and strengthening of village digital infrastructure are necessary to ensure the optimalization of the village website.